Relative age effects in Swiss junior soccer and their relationship with playing position - Romann, M.; Fuchslocher, J. (European Journal of Sport Science, 2013)
Relative age effects (RAEs) refer to age differences between children in the same selection year. The present study investigated the prevalence of RAEs and their link to playing positions in Swiss junior soccer. Swiss male junior soccer players (n=50,581) representing 11% of the age-matched population - members of extra-curricular soccer teams - were evaluated to determine the influence of RAEs on Swiss junior soccer. Subgroups were the national talent development programme (n=2880), and U-15 to U-21 national teams (n=630). While no RAEs were found for the self-selected extra-curricular soccer teams or for the U-20 teams (P>0.05), significant RAEs were found for talent development and the national U-15 to U-19 and U-21 teams (P<0.01). Additionally, defenders born early in the year were significantly overrepresented compared with goalkeepers, midfielders and strikers (P<0.05). In Switzerland, RAEs apparently have substantial influence on the talent identification process for U-15 to U-18 teams, significantly influencing the selection of players in talent development teams already at an early age, but do not influence self-selected participation in extra-curricular soccer. Additionally, the RAE bias may be a predictor of playing positions in national teams. To minimise RAEs in Swiss soccer, systematic education for all coaches regarding RAEs should be established, in addition to a slotting system with rotating calendar cut-off dates.